Structural Studies of the O‐Acetyl‐Containing O‐Antigen from a Shigella flexneri Serotype 6 Strain and Synthesis of Oligosaccharide Fragments Thereof. Issue 19 (8th May 2013) - Chassagne, Pierre; Fontana, Carolina; Guerreiro, Catherine; Gauthier,, Charles; Phalipon, Armelle; Widmalm, Göran; Mulard, Laurence A.
Abstract: Extensive analysis by NMR spectroscopy of the delipidated lipopolysaccharide of Shigella flexneri serotype 6 strain MDC 2924‐71 confirmed the most recently reported structure of the O‐antigen repeating unit as {→4)‐β‐D ‐Gal p A‐(1→3)‐β‐D ‐Gal p NAc‐(1→2)‐α‐L ‐Rha p 3Ac/4Ac ‐(1→2)‐α‐L ‐Rha p ‐(1→}, and revealed the non‐stoichiometric acetylation at O‐3C /4C . Input from the CASPER program helped to ascertain the fine distribution of the three possible patterns of O ‐acetylation. The non‐ O ‐acetylated repeating unit (ABCD) corresponded to about 2/3 of the population, while 1/4 was acetylated at O‐3C (3Ac CDAB), and 1/10 at O‐4C (4Ac CDAB). Di‐ to tetrasaccharides with a Gal p A residue (A) at their reducing end were synthesized as their propyl glycosides following a multistep linear strategy relying on late‐stage acetylation at O‐3C . Thus, the 3C ‐ O ‐acetylated and non‐ O ‐acetylated targets were synthesized from common protected intermediates. Rhamnosylation was most efficiently achieved by using imidate donors, including at O‐4 of a benzyl galacturonate acceptor. In contrast, a thiophenyl 2‐deoxy‐2‐trichloroacetamido‐D ‐galactopyranoside precursor was preferred for chain elongation involving residue B. Final Pd/C‐mediated deprotection ensured O ‐acetyl stability. All of the target molecules represent parts of the O‐antigen of S. flexneri 6, a prevalent serotype. Non‐ O ‐acetylated oligosaccharides are also fragments of the Escherichia coli O147 O‐antigen. Abstract : The repeating unit of the O‐specific polysaccharide (PS) from Shigella flexneri serotype 6 (SF6) strain MDC 2924‐71 has been studied by NMR spectroscopy, confirming a non‐stoichiometric O ‐acetylation at one of the rhamnosyl residues. The synthesis of di‐ to tetrasaccharide derivatives with and without mono‐ O ‐acetylation is reported. Structures are common to SF6, SF6a, and Escherichia coli O147.